Work-family and family-work conflicts and health: the protective role of work engagement and job-related subjective well-being - Anna M. Zalewska (Nofer Institute of Occupational Medicine, 2020)
Background The aim of this study was to analyze the relationships between work-family conflict (WFC) and family-work conflict (FWC) and mental health, considering variables that can regulate (mediate or moderate) these relationships: work engagement and job-related subjective well-being (job satisfaction, positive - PA and negative - NA affects at work). Material and Methods A total of 114 employees (31.6% of whom were men), aged 25-55 (M = 35.39, SD = 7.42), completed a set of questionnaires in the Polish version: Work-Family Conflict and Family-Work Conflict , Utrecht Work Engagement Scale (UWES-17), Job Affect Scale , Job Satisfaction Scale , and General Health Questionnaire GHQ-28. Results Relations between all variables were consistent with expectations, besides an insignificant FWC-health correlation. The models of relationships (designed separately for WFC and FWC) tested in SEM analyses were very well-fitted to data. Each conflict positively predicted NA and, through NA, it also indirectly predicted health troubles. Each conflict also predicted negatively work engagement and, through it, it indirectly affected job satisfaction and PA, then indirectly NA and health troubles. However, the beneficial indirect effect of engagement on health was stronger than the indirect WFC/FWC effect - higher work engagement predicted higher job satisfaction and PA, which in turn predicted negatively NA and health troubles. Mental health was directly predicted by PA (it decreased problems, i.e., enhanced health) and NA (it increased problems, i.e., weakened health), and additionally by the WFC and work engagement interplay. Conclusions The obtained results confirm that FWC/ WFC-health relationships are complex and mediated by work engagement and job-related SWB dimensions. They also show that higher work engagement increases job-related SWB and indirectly enhances mental health. Additionally, its high level is a buffer of direct adverse effects of WFC on health. Increasing work engagement in the context of high FWC, and especially WFC, can be helpful in preventing their negative effects on health. Med Pr. 2020;71(1):33-46